Extracellular vesicles from parasitic helminths and their potential utility as vaccines - Gebeyaw Getnet Mekonnen; Mark Pearson; Alex Loukas; Javier Sotillo (Taylor & Francis Group, 2018)
Introduction: Helminths are multicellular parasites affecting nearly three billion people worldwide. To orchestrate a parasitic existence, helminths secrete different molecules, either in soluble form or contained within extracellular vesicles (EVs). EVs are secreted by most cell types and organisms, and have varied roles in intercellular communication, including immune modulation and pathogenesis. Areas covered: In this review, we describe the nucleic acid and proteomic composition of EVs from helminths, with a focus on the protein vaccine candidates present on the EV surface membrane, and discuss the potential utility of helminth EVs and their constituent proteins in the fight against helminth infections. Expert commentary: A significant number of proteins present in helminth-secreted EVs are known vaccine candidates. The characterization of helminth EV proteomes will shed light on host-pathogen interactions, facilitate the discovery of new diagnostic biomarkers, and provide a novel approach for the development of new control measures against helminth infections.